Goals-of-care decision aid for critically ill patients with TBI: Development and feasibility testing. (14th July 2020) - Muehlschlegel, Susanne; Hwang, David Y.; Flahive, Julie; Quinn, Thomas; Lee, Christopher; Moskowitz, Jesse; Goostrey, Kelsey; Jones, Kelsey; Pach, Jolanta J.; Knies, Andrea K.; Shutter, Lori; Goldberg, Robert; et al.
Abstract : Objective: To develop and demonstrate early feasibility of a goals-of-care decision aid for surrogates of patients who are critically ill with traumatic brain injury (ciTBI) that meets accepted international decision aid guidelines. Methods: We developed the decision aid in 4 stages: (1) qualitative study of goals-of-care communication and decision needs of 36 stakeholders of ciTBI (surrogates and physicians), which informed (2) development of paper-based decision aid with iterative revisions after feedback from 52 stakeholders; (3) acceptability and usability testing in 18 neurologic intensive care unit (neuroICU) family members recruited from 2 neuroICU waiting rooms using validated scales; and (4) open-label, randomized controlled feasibility trial in surrogates of ciTBI. We performed an interim analysis of 16 surrogates of 12 consecutive patients who are ciTBI to confirm early feasibility of the study protocol and report recruitment, participation, and retention rates to date. Results: The resultant goals-of-care decision aid achieved excellent usability (median System Usability Scale 87.5 [possible range 0–100]) and acceptability (97% graded the tool's content as "good" or "excellent"). Early feasibility of the decision aid and the feasibility trial protocol was demonstrated by high rates of recruitment (73% consented), participation (100%), and retention (100% both after the goals-of-care clinician–family meeting and at 3 months) and complete data for the measurements of all secondary decision-related and behavioral outcomes to date. Conclusions: Our systematic development process resulted in a novel goals-of-care decision aid for surrogates of patients who are ciTBI with excellent usability, acceptability, and early feasibility in the neuroICU environment, and meets international decision aid standards. This methodology may be a development model for other decision aids in neurology to promote shared decision-making.